Cross-modal retrieval: a review of methodologies, datasets, and future perspectives - Han, Zhichao; Azman, Azreen Bin; Rina Binti Mustaffa, Mas; Binti Khalid, Fatimah (Institute of Electrical and Electronics Engineers Inc., 2024)
With the rapid development of science and technology, all types of mixed media contain large amounts of data. Traditional single multimedia data can no longer satisfy daily requirements. Therefore, the cross-modal retrieval technology has become an urgent requirement. Consequently, there is a pressing need for cross-modal retrieval technology. Its purpose is to mine the connection between different modal samples, that is, to retrieve another modal sample with approximate semantics through one modal sample. For example, users can retrieve multimedia data such as images or videos with text. However, there are differences in the modal representation of different types of multimedia data, and measuring the correlation between different modes is the main problem of cross-modal retrieval. Currently, the most popular deep learning methods have achieved remarkable results in the field of data processing and graphics. Many researchers have applied deep learning methods to cross-modal retrieval to solve the problem of similarity measurement between different multimedia data. By summarizing the relevant paper methods of cross-modal retrieval, this paper provides a definition of cross-modal retrieval problems, reviews the core ideas of the current mainstream cross-modal retrieval methods in the form of three main methods, lists the commonly used data sets and evaluation methods, and finally analyzes the problems and future research trends of cross-modal retrieval.